SYNTHESIS AND CHARACTERIZATION OF ALGINATE-CARBOXYMETHIL CELLULOSE BEADS FROM CORN STALK (Zea mays) WITH CROSSLINK VARIATION C4H6O4Zn - Latifah, Annazmil Fayros; Yulianti, Eny; Khoiroh, Lilik Miftahul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Corn stalk has a high cellulose content, so that it is potential to be used as a composition for making alginate-carboxymethyl cellulose beads. Alginate and cellulose are biodegradable, renewable and non-meltable polymers that have wide applications in various industrial sectors. The purpose of this study was to determine the effect of crosslinking agent C4H6O4Zn on the adsorption and shape of beads. The varied concentrations of C4H6O4Zn are 3%; 5% and 10%. Characterization of alginate-carboxymethyl cellulose beads composites using Fourier Transform InfraRed (FTIR), and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). Based on research, the highest swelling value is obtained at 5% C4H6O4Zn crosslink which is 59.68%. FTIR data shows the appearance of wave numbers at 1413 cm-1 which indicates the presence of C-O Na groups, while at wave number 458 cm-1 indicates the presence of Zn-O groups. SEM-EDX data with a 5% C4H6O4Zn crosslink has a round shape with a wrinkled surface, multiple grooves causing a non-homogeneous surface. Whereas in C4H6O4Zn 10% the surface is almost smooth